Influence of Different β-Blockers on Platelet Aggregation in Patients With Coronary Artery Disease on Dual Antiplatelet Therapy. (January 2016) - Ignjatovic, Vladimir; Pavlovic, Sinisa; Miloradovic, Vladimir; Andjelkovic, Nebojsa; Davidovic, Goran; Djurdjevic, Predrag; Stolic, Radojica; Iric-Cupic, Violeta; Simic, Ivan; Ignjatovic, Vesna D.; Petrovic, Njegos; Smiljanic, Zorica; et al.
Introduction: The use of β-blockers in the treatment of patients with coronary heart disease is associated with a decrease in the frequency of angina pectoris and mortality of patients. Due to the severity of the disease and previous cardiovascular interventions, many patients with coronary artery disease (CAD) use dual antiplatelet therapy to achieve greater inhibition of platelet aggregation. The influence of β-blockers on platelet aggregation in patients using antiplatelet therapy is not well understood. Objective: To examine the effect of different β-blockers on platelet aggregation in patients on dual antiplatelet therapy. Methodology: The study included 331 patients who were treated at the Department of Cardiology, Clinical Center Kragujevac during 2011. Patients were divided into 4 groups depending on the type of β-blockers that were used (bisoprolol, nebivolol, metoprolol, and carvedilol). Platelet aggregation was measured using the multiplate analyzer and expressed through the value of adenosine diphosphate (ADP) test (to assess the effect of clopidogrel), ASPI test (to assess the effect of acetyl salicylic acid), TRAP test (to assess baseline platelet aggregation), and the ratio of ADP/TRAP and ASPI/TRAP ASPI/TRAP (ASPI - aranchidonic acid induced aggregation, TRAP - thrombin receptor activating peptide) representing the degree of inhibition of platelet aggregation compared to the basal value. In consideration were taken the representation of demographic, clinical characteristics, laboratory parameters, and cardiovascular medications between the groups. Results: Patients who used nebivolol had a significantly lower value of the ratio of ADP/TRAP (0.39 ± 0.30) compared to patients who used bisoprolol (0.48 ± 0.26; P = .038), and trend toward the lower values of ADP test (328.0 ± 197.3 vs 403.7 ± 213.2; P = .059), while there was no statistically significant difference in values of other laboratory parameters of platelet function between other groups. Conclusion: Patients with CAD on dual antiplatelet therapy who used nebivolol had significantly lower levels of residual ADP-induced platelet aggregation compared to baseline than patients who used bisoprolol.